2015
DOI: 10.1111/jcpe.12433
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐B lymphocyte immunotherapy is associated with improvement of periodontal status in subjects with rheumatoid arthritis

Abstract: Anti-B lymphocyte therapy could be beneficial to improve periodontitis suggesting a major role of B cells in this disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
45
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 30 publications
3
45
1
Order By: Relevance
“…Quality of information in non‐randomized clinical studies was considered high level in seven articles and moderate in the remaining studies . Quality of information in the In vivo animal studies was considered moderate in five articles and high in seven studies .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Quality of information in non‐randomized clinical studies was considered high level in seven articles and moderate in the remaining studies . Quality of information in the In vivo animal studies was considered moderate in five articles and high in seven studies .…”
Section: Resultsmentioning
confidence: 99%
“…registered a positive effect on the periodontium at 6 months in patients with AS and on anti‐TNF‐α, but not in patients with RA. Therapies based on anti‐IL‐6, anti‐IL‐1 and anti‐CD20 also show a delay in the progression of P, as well as an improvement of the periodontal status of the patients (Table ). In accordance with the clinical studies, most experimental in vivo animal studies show that anti‐cytokines BMs were consistently associated with improvement of the periodontal status expressed as reduction of inflammatory infiltrate, level of local and systemic cytokines number of osteoclasts, alveolar bone loss, lesion size and preservation of collagen network .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Case-control studies found a more prevalent and severe periodontal disease (PD) status in RA patients (Al-Shammari, Al-Khabbaz, Al-Ansari, Neiva, & Wang, 2005;Bozkurt, Yetkin Ay, Berker, Tepe, & Akkus, 2006), as well as a reduction in the clinical parameters of active RA following effective periodontal treatment and control of periodontal infection (Al-Katma, Bissada, Bordeaux, Sue, & Askari, 2007;Bıyıkoğlu et al, 2013;Ortiz et al, 2009). On the other hand, clinical parameters of periodontal disease were improved in RA patients under treatment with anti-B lymphocyte therapy (Coat et al, 2015). However, it is remains unclear whether there is an etiological link between these two chronic inflammatory diseases, or whether the epidemiological results are due to statistical bias reinforced by the common risk factors (Farquharson, Butcher, & Culshaw, 2012).…”
mentioning
confidence: 99%
“…IgD-deficient mice have a delay in B cell affinity maturation, exhibit diminished B cell activation, and are significantly protected against periodontal bone loss versus WT controls (9). 6) Importantly, a clinical trial showed that anti-B cell therapy with anti-CD20 mAb in individuals with arthritis significantly reduced indices of clinical periodontal inflammation and tissue destruction, thus implicating B cells in periodontal pathogenesis (10). Together, B cells are not only abundant and a major source of RANKL (3) but they are also causally involved in periodontitis.…”
mentioning
confidence: 99%